BLOOD ANTIGENICITY & PERSONALITY - DR JAYANT J MAKWANA (International Journal of Pharma and Bio Sciences, 2016)
Effect of blood group antigen on personality was studied in 400 participants aged 18-60 years in Department of Physiology of R D Gardi Medical College. The personality assessment was done with the help of standard personality inventory. Blood group was determined with slide agglutination method. It was observed that blood group ‘O’ individuals were 48.75 % efficient, 49.09% social, 52.15 % emotional,51.94 % challenge acceptor, 48.63% workaholic. Blood group ‘A’ individuals were 45.6 % efficient, 52 % social, 52.9 % emotional, 48 % challenge acceptor, 50.3 % workaholic. Blood group ‘B’ individuals were 47.82 % efficient, 50.53% social, 51.3 % emotional, 51.7 % challenge acceptor, 48.94 % workaholic. Blood group ‘AB’ individuals were 51.43 % efficient, 50 % social, 53.06 % emotional, 46.94 % challenge acceptor, 44.5 % workaholic. So according to our study Individuals with blood group A are more efficient, those with blood group O are more social, blood group B individuals are more emotional & those with blood group AB are more workaholic and accepts the challenge. The results were statistically significant.